1993
DOI: 10.1164/ajrccm/148.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to Domestic Mites in a Cold Temperate Region

Abstract: Factors favoring sensitization to house dust mites (HDM) were studied in a cold, temperate climate in northern Sweden. Sixty-five children previously found to react positively to a skin prick test (SPT) to HDM were included. The SPT to HDM was repeated, and serum IgE antibodies to D. pteronyssinus and D. farinae were determined. HDM, Euroglyphus maynei, Tarsonemus, or storage mites occurred in mattress dust samples from 23 of the 65 homes, and in 10 homes more than 100 HDM/g of mattress dust were found. Mites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 27 publications
8
31
0
Order By: Relevance
“…There are occasional findings of mite sensitization and high levels of mites in house dust in northern Sweden (30). Our finding of a low prevalence of mite sensitization in Vasterbotten was in agreement with Norrman et al's study from the same region (22).…”
Section: Discussionsupporting
confidence: 93%
“…There are occasional findings of mite sensitization and high levels of mites in house dust in northern Sweden (30). Our finding of a low prevalence of mite sensitization in Vasterbotten was in agreement with Norrman et al's study from the same region (22).…”
Section: Discussionsupporting
confidence: 93%
“…Such houses do not conform to architectural regulations and are constructed in the periphery of cities, with poor living conditions such as lack of water, gas and sewerage systems from the municipal network. Previous studies have confirmed that houses with basement floors that have higher frequency of house dust mites are associated with respiratory symptoms when compared with apartments [17,18]. The present study supported the argument that respiratory allergic diseases and respiratory symptoms could be increased among people living in shanty-type houses as compared with those living in apartments.…”
Section: Discussionsupporting
confidence: 89%
“…Although previous studies have not obtained samples from basements, the low floor levels of houses (ie, ground or first floors) have been shown to have significantly higher concentrations of Der f 1 and Der p 1 allergens than the higher floor levels. 19,22,37 Thus, it appears that basements are notable reservoirs of HDM allergens for dogs and are also unrecognized reservoirs of HDM allergens for humans.…”
Section: Discussionmentioning
confidence: 99%